2021
DOI: 10.1111/apha.13625
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the biological relevance of standardized high‐resolution respirometry to assess mitochondrial function in permeabilized human skeletal muscle

Abstract: Aim This study sought to provide a statistically robust reference for measures of mitochondrial function from standardized high‐resolution respirometry with permeabilized human skeletal muscle (ex vivo), compare analogous values obtained via indirect calorimetry, arterial‐venous O2 differences and 31P magnetic resonance spectroscopy (in vivo) and attempt to resolve differences across complementary methodologies as necessary. Methods Data derived from 831 study participants across research published throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 145 publications
(406 reference statements)
0
12
1
Order By: Relevance
“…We here presented the two groups together and thereby we are lacking an appropriate control group not being subjected to the intervention. The mitochondrial respiratory measurements in this study are somewhat lower (~33%) than expected in a population with a VO 2max of 65 ml • kg -1 • min -1 [69]. The reason for this is unknown but could be related to lower degrees of mechanical permeabilization during the dissection of the muscle bundles.…”
Section: Discussioncontrasting
confidence: 60%
“…We here presented the two groups together and thereby we are lacking an appropriate control group not being subjected to the intervention. The mitochondrial respiratory measurements in this study are somewhat lower (~33%) than expected in a population with a VO 2max of 65 ml • kg -1 • min -1 [69]. The reason for this is unknown but could be related to lower degrees of mechanical permeabilization during the dissection of the muscle bundles.…”
Section: Discussioncontrasting
confidence: 60%
“…Even though the enzyme is not rate limiting for the flux through the Krebs cycle (Blomstrand et al, 1997 ), SDH activity has shown to be proportional to the ex vivo O 2max of intact single muscle fibers and myocardial trabeculas in hyperoxia (van der Laarse et al, 1989 ; Des Tombe et al, 2002 ). Interestingly, both OXPHOS and SDH activity have also shown to be closely related to the O 2max of quadriceps muscles during one-legged exercise (Blomstrand et al, 1997 ; Jacobs and Lundby, 2021 ) and to body-mass-specific O 2max in humans (Costill et al, 1976 ; van der Zwaard et al, 2016a ; Jacobs and Lundby, 2021 ). Recent observations in 68 cardiac patients, controls and elite cyclists demonstrated that mitochondrial oxidative capacity determined from SDH activity even scales proportionally with body-mass-specific O 2max during cycling, ranging 9.8–79.0 mL·kg −1 ·min −1 (van der Zwaard et al, 2016a ).…”
Section: The Overlooked Underlying Physiology: Skeletal Muscle Determinants Of Endurance Performancementioning
confidence: 99%
“…Notably, these values exceed the greatest values estimated or measured for mammalian mitochondria by an order of magnitude. Simulations were also run with upper limit measured values from high-resolution respirometry of isolated mitochondria/muscle tissue and full body respiratory measurements, of which the latter exceed the former by a factor of three [ 53 , 54 ]. Simulations were performed with these extreme values for maximal consumption rate in order to determine the steepest gradients plausible.…”
Section: Methodsmentioning
confidence: 99%